Effectiveness of 38% Silver Diamine Fluoride in Reducing Dentine Hypersensitivity on Exposed Root Surface in Older Chinese Adults: Study Protocol for a Randomised Double-Blind Study - Alice Kit Ying Chan; Manisha Tamrakar; Chloe Meng Jiang; Yiu Cheung Tsang; Katherine Chiu Man Leung; Chun Hung Chu (MDPI AG, 2022)
Background: Dentine hypersensitivity on an exposed root surface induces pain, affects daily oral hygiene practice, limits dietary choices and negatively affects quality of life. Silver diamine fluoride is marketed in the United States as a desensitising agent, but well-designed clinical trials are limited. This study evaluates the anti-hypersensitivity effect of silver diamine fluoride on hypersensitive teeth due to an exposed root surface in older Chinese adults. Methods/design: We will conduct a randomised double-blind clinical trial with a sample size of at least 148 Chinese older adults aged 65 or above who have dentine hypersensitivity due to an exposed root surface. We will collect written consent before the study. A trained examiner will examine the participants' teeth with a blast of compressed air from a 3-in-1 syringe. Those adults who report a self-perceived sensitivity score (SS) (0 to 10) of 8 or more on at least one tooth with an exposed root surface will be recruited. The recruited older adults will be randomly allocated into two groups using a block randomisation of six. Group 1 participants will receive the application of 38% silver diamine fluoride solution every 4 weeks. Group 2 participants will receive the application of 5% potassium nitrate solution every 4 weeks. Dietary advice, oral hygiene instruction and fluoride toothpaste at 1450 ppm will be provided to participants in both groups. The same trained examiner will perform follow-up examinations for the participants and determine the dentine hypersensitivity in SS of the most hypersensitive tooth (with the highest pre-treatment SS) immediately after the intervention and at 4-week and 8-week intervals. Discussion: There is no consensus on the standard of care for a professionally applied desensitising agent in older adults. This trial will provide evidence for clinicians to devise an effective dental care plan for older adults with dentine hypersensitivity. Trial registration: NCT05392868 Registered on 22 May 2022.